Analisis Spasial Dampak Pariwisata Terhadap Kondisi Sosial Ekonomi Masyarakat - Yuniarti Ibrahim; Sri Maryati; M.Iqbal Liayong Pratama (Jurnal Penelitian Pendidikan Geografi, 2025)
Tourism is a strategic sector that contributes to local economic development and cultural preservation; however, its impact on the socio-economic conditions of local communities is often not thoroughly analyzed, particularly from a spatial perspective. This study aims to analyze the spatial impact of tourism on the socio-economic conditions of communities in Kabila Bone District. A qualitative approach was used by integrating data obtained from interviews, questionnaires, observations, and documentation, along with spatial analysis using Geographic Information Systems (GIS). Respondents were selected through purposive sampling. The data were analyzed through reduction, presentation, tabulation using Microsoft Excel, and spatial mapping with GIS software. The results indicate that tourism contributes to improved education (48.48% of residents completed high school/vocational education), additional monthly income of IDR 500,000–1,000,000 (34% of respondents), and the creation of new jobs (21.74%) in the trade, transportation, and cultural sectors. Spatially, Oluhuta and Biluango Villages experience very high socio-economic impacts, Olele and Molotabu are categorized as high, Botubarani as moderate, Huangobotu and Botutonuo as low, while Bintalahe and Modelomo show very low impacts due to limited accessibility and infrastructure. Overall, tourism development has a positive impact on income, business opportunities, and the preservation of local culture in Kabila Bone District.